1991
DOI: 10.1002/bem.2250120202
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism for the influence of weak magnetic fields on biological systems

Abstract: A physical mechanism is suggested for a resonant interaction of weak magnetic fields with biological systems. An ion inside a Ca(2+)-binding protein is approximated by a charged oscillator. A shift in the probability of ion transition between different vibrational energy levels occurs when a combination of static and alternating magnetic fields is applied. This in turn affects the interaction of the ion with the surrounding ligands. The effect reaches its maximum when the frequency of the alternating field is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
273
2
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(296 citation statements)
references
References 10 publications
14
273
2
7
Order By: Relevance
“…Considering EM interactions from a purely physical point of view, several mechanisms have been proposed to account for the initial interactions with cells (Liboff et al, 1987;Lednev, 1991;Blanchard and Blackman, 1994), but these models have been limited by their inability to account for the wide range of experimental observations. The Mobile Charge Interaction (MCI) model (Blank, 1995a), based on simple physical interactions, grew out of a wide range of experiments.…”
mentioning
confidence: 99%
“…Considering EM interactions from a purely physical point of view, several mechanisms have been proposed to account for the initial interactions with cells (Liboff et al, 1987;Lednev, 1991;Blanchard and Blackman, 1994), but these models have been limited by their inability to account for the wide range of experimental observations. The Mobile Charge Interaction (MCI) model (Blank, 1995a), based on simple physical interactions, grew out of a wide range of experiments.…”
mentioning
confidence: 99%
“…More hydroxyl (OH -) ions are created to form alkaline molecules, and reduce acidity, for this reason cancer cells do not survive well in an alkaline environment. 45 Some animal studies have concluded that the magnetization of water increased the permeability through cell membranes, 46 and that the magnetic field directly affected intracellular fluid and intracellular substances to activate enzymes inside the cells and to accelerate biochemical reactions in the body. 47 Previous studies with magnetized water, reported that the long-term intake of magnetized water (over 8 weeks) may be beneficial in both prevention and treatment of complications in diabetic, treatment effect of magnetized water not only decreased the blood glucose and glycated hemoglobin levels but also reduced blood and liver DNA damages in STZ-induced diabetic rats.…”
Section: Resultsmentioning
confidence: 99%
“…It is pertinent to infer that exposure to magnetic fields induces quite a variety of biological effects. Different waveform magnetic field sources results in varied biological effects on living systems, as their frequency spectrums are diverse [39,58,59]. …”
Section: Discussionmentioning
confidence: 99%